Switzerland : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper and Statistical Appendix compares two alternative time series approaches to analyzing Switzerland's recent business cycle experience: first, the traditional 'smooth-trend-plus-cycle approach,' which envisages observed output growth as fluctuating around a relatively smooth potential output growth path; and, second, the more recently developed 'regime change approach,' which views business cycles as shifts between 'high-growth' states (expansions) and 'slow-growth' states (recessions) of the economy. The paper also examines Switzerland's monetary policy framework, and describes the challenges to the Swiss tax system.